2021
DOI: 10.3389/fonc.2021.698197
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Auxiliary Diagnostic Biomarkers for Multiple Myeloma: A Systematic Review, Meta-Analysis, and Recommendations

Abstract: Multiple myeloma (MM) is a hematologic malignancy characterized by aberrant expansion of monoclonal plasma cells with high mortality and severe complications due to the lack of early diagnosis and timely treatment. Circulating miRNAs have shown potential in the diagnosis of MM with inconsistent results, which remains to be fully assessed. Here we updated a meta-analysis with relative studies and essays published in English before Jan 31, 2021. After steps of screening, 32 studies from 11 articles that included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Several studies have shown that miRNAs are present in peripheral blood and can be biomarkers for various diseases. 125,126 For example, in a study by Xiang et al, researchers investigated the expression levels of miRNAs in the peripheral blood of patients with MM. They found that specific miRNAs were differentially expressed in MM patients compared to healthy controls, suggesting their potential as diagnostic biomarkers.…”
Section: Mirnas As Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that miRNAs are present in peripheral blood and can be biomarkers for various diseases. 125,126 For example, in a study by Xiang et al, researchers investigated the expression levels of miRNAs in the peripheral blood of patients with MM. They found that specific miRNAs were differentially expressed in MM patients compared to healthy controls, suggesting their potential as diagnostic biomarkers.…”
Section: Mirnas As Biomarkersmentioning
confidence: 99%
“…They found that specific miRNAs were differentially expressed in MM patients compared to healthy controls, suggesting their potential as diagnostic biomarkers. 125…”
Section: Mirnas In Peripheral Bloodmentioning
confidence: 99%
“…In MM, miR-4254 was found to be the most promising diagnostic biomarker [ 115 ]. In addition, a combination of up-regulated miR-34a and down-regulated let-7e could distinguish MM from both control and monoclonal gammopathy of undetermined significance (MGUS) with high sensitivity and specificity [ 116 ].…”
Section: Clinical Applications Of Mirnas Focusing On Hematological Ma...mentioning
confidence: 99%